Study on Heavy Metal Adsorption Capacity According to Modification Conditions with K-Zeolite - Wang, Jei-Pil; Ganzorig, Chimeddorj (International Journal of Membrane Science and Technology, 2023)
In this study, synthetic zeolites were prepared using a sample obtained by removing Li from used LAS (Li2O-Al2O3-SiO2) crystallized glass, which is a material for induction top plates, through a sulfuric acid heat reaction. The removal experiment of heavy metals (Pb, Cd, Cr6+, Hg) ions present in wastewater was conducted. Two types of zeolites were used for heavy metal adsorption: before and after K+ modification. The changes in the amount of heavy metal adsorption were investigated depending on the adsorption reaction conditions, such as the amount of zeolite used as an adsorbent, adsorption time, concentration of heavy metal elements, and pH. K-zeolite showed an average improvement of 54.5% for Cr6+ and 79.5% for Hg compared to the conventional lithium removal zeolite. According to the experimental results of heavy metal removal under various conditions, the heavy metal adsorption removal rate increased as the amount of zeolite added increased. It was confirmed that the adsorption reaction time had a significant impact on the adsorption characteristics, and in particular, the removal rate of Cd greatly improved. For Cd, the removal rate improved as the pH increased, while for Pb and Cr6+, the removal rate improved as the pH decreased. The removal rate of Hg was found to be similar across the entire pH range.